Effects of fish species composition on Diphyllobothrium spp. infections in subarctic brown trout - is three-spined stickleback a key species? - Kuhn, Jesper A.; Frainer, André; Knudsen, Rune; Kristoffersen, Roar; Amundsen, Per-Arne (Journal of Fish Diseases, 2016)
Accepted manuscript version. Published version available in Effects of fish species composition on Diphyllobothrium spp. infections in subarctic brown trout - is three-spined stickleback a key species? (2016) 39(11), s.1313-1323. . Subarctic populations of brown trout (Salmo trutta) are often heavily infected with cestodes of the genus Diphyllobothrium, assumedly because of their piscivorous behavior. This study explores possible associations between availability of fish prey and Diphyllobothrium spp. infections in lacustrine trout populations. Trout in i) allopatry (group T); ii) sympatry with Arctic charr (Salvelinus alpinus) (group TC); and iii) sympatry with charr and three-spined stickleback (Gasterosteus aculeatus) (group TCS) were contrasted. Mean abundance and intensity of Diphyllobothrium spp. were higher in group TCS compared to group TC and group T. Prevalence however was similarly higher in group TCS and group TC compared to group T. Zero-altered negative binomial modelling identified lowest probability of infection in group T and similar probabilities of infection in group TC and group TCS, whereas the highest intensity was predicted in group TCS. Evidently, the most infected trout were from the group co-occurring with stickleback (TCS), assumedly due to a high availability of suitable prey fishes. In conclusion, our study demonstrates elevated Diphyllobothrium spp. infections in lacustrine trout populations where fish prey are available, and suggests that highly available and easily caught stickleback prey may play a key role in the transmission of Diphyllobothrium spp. parasite larvae.